The Effect of Project-Based Learning Methods on Students' Ability in Developing Research Instruments of CDA - Noermanzah Noermanzah; Suryadi Suryadi; Syafryadin Syafryadin (Journal of English Education and Teaching, 2023)
The better the collaboration in developing a class discourse analysis research instrument, the better the research instrument's preparation outcomes. Thus, this study aims to determine the effect of project-based learning methods on students' ability to develop discourse analysis research instruments in the Indonesian Language Education Masters Study Program at the University of Bengkulu. The One Groups Pretest-Posttest Design was utilized in this work as an experimental approach utilizing pre-experimental designs (non-designs). The data collection technique used was a test technique in the form of a performance test to arrange research instruments of class discourse analysis. The steps for analyzing the data are by giving an assessment score, calculating the average student score, testing the normality of the data, and testing the hypothesis with the Paired Sample T Test using SPSS 24. The results showed a significant effect of project-based learning methods on students' abilities in composing a discourse analysis research instrument for Indonesian Language Education Study Program graduate students. The influence is indicated by the Sig value (2-tailed) of 0.00 is smaller than 0.05. Students have mastered the ability to compose class discourse analysis research instruments, namely making transcriptions of spoken discourse into written text, compiling guidelines for class discourse analysis in the form of work analysis tables and coding, and compiling interview guidelines. Keywords: Effects, project-based learning methods, the ability to compose class discourse analysis research instruments